Pengaruh Kepuasan Masyarakat, Lingkungan Kerja, Motivasi Kerja, Disiplin Kerja dan Kepemimpinan Terhadap Pelayanan Publik di MPP Kota Batam dengan Kinerja Pegawai Sebagai Mediasi - Yuswardi, Yuswardi; Fatyandri, Adi Neka; Ananda, Anggun Dea (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
Public services that have high quality standards, often referred to as excellent services, refer to the best services that meet certain standards. Service standards act as guidelines for providing services and are the basis for assessing the quality of these services. This standard is not only a reference in providing quality services, but also reflects the commitment and promise of service providers to the community. This research method is to use a non-probability sampling technique, namely a purposive sampling method where the sample is not carried out randomly but can be adjusted to predetermined criteria. This sampling was of course carried out by giving questionnaires to respondents who met the criteria expected in this research, namely the public and public service employees were only able to fill out this questionnaire. This research was carried out by distributing questionnaires as a medium for collecting research data obtained from respondents. The research carried out can be broken down into analytical studies involving the role of employees as mediators in the relationship between several factors, such as community satisfaction, work environment, work motivation, work discipline and leadership, on public services in MPP Batam City. This research is related between these variables to understand how employee performance can mediate the influence of these factors on public services.